Environmental management of social dilemas - VOOGD, Henk (European Spatial Research and Policy, 1995)
Social dilemmas are contradictions between the interests of individuals and the collective interests as expressed in plans and policy proposals. It is argued in this paper that if these social dilemmas are denied in environmental planning then this may have detrimental consequences in the long run for urban ecology and society. Planning proposals can only be appropriately implemented if behavioural aspects of various actors are fully taken into account. Trade-offs are essential in planning to arrive at compromise solutions. The concept of 'sustainability', however, does not al low compromises. In this paper a plea is given to shift the attention in urban environmental planning from the 'sustainability' concept to the 'quality' concept.